Islam Nusantara in Song: Transitivity Benchmarking on Qasidah Nahdliyah - Suparno, Darsita; Rokhim, Minatur; Chairul, Syifa Fauzia; Atih, Idris (Studia Islamika, 2025)
This study examines the representation of patriotic, social, economic, and political values in the lyrics of Qasidah Nahdliyah by KH Afifuddin Muhajir, and its role as a medium of cultural da’wah and the construction of the Islam Nusantara ideology. An interdisciplinary qualitative approach was employed, integrating Systemic Functional Linguistics theory (transitivity analysis) and Critical Discourse Analysis within the framework of national history and pesantren culture. Data in the form of song lyrics were analyzed textually. The findings reveal a dominance of material processes that represent Nahdlatul Ulama’s active role in safeguarding Islamic creed, strengthening social solidarity, and responding to contemporary challenges. Religious symbolism in the text underscores NU’s role as a spiritual guardian and protector of inclusive nationalism. This Qasidah is positioned as a religious expression and an ideological vehicle that supports moderate Islam and cultural nationalism while rejecting socio-political fragmentation. The study’s limitation lies in the lack of analysis of multimodal aspects and audience reception. This research contributes to strengthening linguistic analysis of religious discourse in the context of Indonesian Islamic cultural artifacts.